Genome-wide association study for the primary feather color trait in a native Chinese duck - Sun, Yanfa; Wu, Qiong; Lin, Rulong; Chen, Hongping; Zhang, Min; Jiang, Bingbing; Wang, Yaru; Xue, Pengfei; Gan, Qiuyun; Shen, Yue; Chen, Feifan; Liu, Jiantao; et al. (Frontiers in Genetics, 2023)
Background: To reveal candidate genes and the molecular genetic mechanism underlying primary feather color trait in ducks, a genome-wide association study (GWAS) for the primary feather color trait was performed based on the genotyping-by-sequencing (GBS) technology for a native Chinese female duck, Longyan Shan-ma ducks. Methods: Blood genomic DNA from 314 female Longyan Shan-ma duck were genotyped using GBS technology. A GWAS for the primary feather color trait with genome variations was performed using an univariate linear mixed model based on all SNPs in autosomes. Results: Seven genome-wide significant single nucleotide polymorphisms (SNPs, Bonferroni-adjusted P-value < 8.03 ×10-7) within the introns of the genes STARD9, ZNF106, SLC7A5, and BANP genes were associated with the primary feather color trait. Twenty-two genome-wide suggestive SNPs (Bonferroni-adjusted P-value < 1.61 ×10-5) of 17 genes (besides ZNF106 and SLC7A5) were also identified. Seven SNPs were located at one 0.22 Mb region (38.65-38.87 Mb) on chromosome 5, and six SNPs were located at one 0.31 Mb region (19.53-19.84 Mb) on chromosome 11. The functions of STARD9, SLC7A5, BANP, LOC101798015, and IPMK were involved pigmentation and follicle development, especially, STARD9 up-regulated expression in black feather (haplotype-CCCC) bulb tissue compared with in pockmarked feather (haplotype-TGTT) bulb tissue, implicating these genes as candidate genes for primary feather color trait. Conclusions: The preliminarily findings suggested candidate genes and regions, and the genetic basis of primary feather color trait in a female duck.